Determinants of paddy farmers demographic factors on unsustainability farm practices - Terano, Rika; Mohamed, Zainalabidin; Sharifuddin, Juwaidah; Ali, Fazlin (Auctores Publishing, 2018)
Sustainable agriculture is closely related to farming practices. There are many farming practices such as land preparation, use of fertilizers and weedicides among other indicators of farming practices that lead to sustainable agriculture. In particular, weed and pest control are focal points for certain crops such as cotton, rice, vegetables, and fruit with heavily applied chemical inputs which cause unsustainability in farming. Among food crops, paddy requires enormous doses of fertilizers, weedicides, and pesticides to keep it healthy and productive. The objective of this study is to determine the factors that contribute to the unsustainability of paddy farming practices at field level via Paddy Farmer Sustainability Index (PFSI) based on the current 33 paddy farming practices. Tobit regression analysis found that knowledge and awareness played essential roles as the determinant of unsustainability level in paddy farming.